Asciminib in the Treatment of Philadelphia Chromosome-Positive Chronic Myeloid Leukemia: Focus on Patient Selection and Outcomes - Hijiya N; Mauro MJ (Cancer Management and Research, 2023)
Nobuko Hijiya,1,* Michael J Mauro2,* 1Division of Pediatric Hematology, Oncology, and Stem Cell Transplantation, Columbia University Irving Medical Center, New York, NY, USA; 2Myeloproliferative Neoplasms Program, Leukemia Service, Memorial Sloan Kettering Cancer Center, New York, NY, USA*These authors contributed equally to this workCorrespondence: Nobuko Hijiya, Columbia University Irving Medical Center, 161 Fort Washington Ave, HIP-7, New York, NY, 10032, USA, Tel +1 212 305 9770, Email nh2636@cumc.columbia.eduAbstract: Tyrosine kinase inhibitors (TKIs) have significantly changed the treatment of chronic myeloid leukemia (CML) and improved outcomes for patients with CML in chronic phase (CML-CP) and accelerated phase (AP). Now armed with numerous effective therapeutic options, clinicians must consider various patient- and disease-specific factors when selecting the most appropriate TKI across lines of therapy. While most patients with CML expected to have a near-normal life expectancy due to the success of TKIs, emphasis has expanded beyond response and survival to include factors like quality of life, tolerability, and long-term toxicity management. Importantly, a subset of patients can achieve sustained deep molecular response and can attain treatment-free remission. Despite these successes, unmet needs remain related to CML treatment, including the persistent challenge of treatment resistance and intolerance, broadening treatment options for patients with resistance mutations or serious comorbidities, and focus on specific populations such as children and young adults. In particular, the only previously available treatments for patients with CML-CP with the T315I mutation were ponatinib, olverembatinib (exclusively approved for use in China at the time of this writing), omacetaxine, and hematopoietic stem cell transplantation. Asciminib has entered the CML treatment landscape as a new option for adult patients with CML-CP who have received ≥ 2 prior TKIs or those with the T315I mutation. Asciminib’s unique mechanism of action, Specifically Targeting the ABL Myristoyl Pocket, sets it apart from traditional adenosine triphosphate-competitive TKIs. While asciminib may overcome unmet needs for patients with CML-CP and continues to be studied in other novel settings, guidance on how to integrate asciminib in treatment algorithms is needed. This review focuses on clinical data and how asciminib can overcome current unmet needs, discusses how to individualize patient selection, and highlights future directions to investigate asciminib in earlier lines of therapy and in children and adolescents.Keywords: asciminib, chronic myeloid leukemia, tyrosine kinase inhibitors, patient selection, pediatrics